2017
DOI: 10.1167/iovs.16-21116
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Metabolomics Reveals Early Dominant Optic Atrophy Signature in Optic Nerves of Opa1delTTAG/+ Mice

Abstract: Our comprehensive metabolomic investigations revealed in symptomatic as well as in presymptomatic Opa1delTTAG/+ mice, a specific sensitiveness of the optic nerve to Opa1 insufficiency, opening new routes for protective therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…25 Interestingly, we also have found decreased concentrations of spermine and spermidine in the optic nerve of a transgenic mouse model of dominant optic atrophy carrying a heterozygous mutation in Opa1. 26 In conclusion, we report a significant plasma metabolomic signature in individuals with XFS characterized by decreased concentrations of the neuroprotective spermine and spermidine polyamines, hypertyrosinemia, and a profile partially overlapping the metabolomic signature of insulin resistance. This observation is intriguing because, to our knowledge, no evidence of insulin resistance has been reported in XFS to date.…”
Section: Discussionmentioning
confidence: 67%
“…25 Interestingly, we also have found decreased concentrations of spermine and spermidine in the optic nerve of a transgenic mouse model of dominant optic atrophy carrying a heterozygous mutation in Opa1. 26 In conclusion, we report a significant plasma metabolomic signature in individuals with XFS characterized by decreased concentrations of the neuroprotective spermine and spermidine polyamines, hypertyrosinemia, and a profile partially overlapping the metabolomic signature of insulin resistance. This observation is intriguing because, to our knowledge, no evidence of insulin resistance has been reported in XFS to date.…”
Section: Discussionmentioning
confidence: 67%
“…35 The significant decrease of spermidine and spermine we reported in the optic nerve of a mouse model of another form of optic neuropathy due to mutations in the OPA1 gene, further illustrates the importance of these metabolites in optic nerve pathophysiology. 36 Thus, spermidine and spermine, which are related to mitochondrial dysfunction, senescence, and RGC damage, are central elements of the POAG signature. We were unable to explain the decreased concentration of histamine in POAG group compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…To date, very few OPA1 dysfunctions have been investigated by omics approaches. Our targeted metabolomic study on 9 tissues of the Opa1 delTTAG/ + mouse model 9 revealed a discriminating pre-symptomatic metabolomic signature in the optic nerves 21 . Apart from the blood, no other tissue showed this type of metabolic signature, indicating that OPA1 dysfunctions target mainly the retinal ganglion cells of the optic nerve.…”
Section: Introductionmentioning
confidence: 89%